Hemophagocytic syndrome and acute pancreatitis in acute systemic lupus erythematosus - Bushra Alblewi; Iqbal A. Bukhari; Manal Hasan; Abdulaziz Alzahani; Raed Bukhari; Layla Bashawri; Muhammad Al Shawarby (Wolters Kluwer Medknow Publications, 2014)
Hemophagocytic syndrome (HPS) is characterized by the activation of histiocytes with prominent hemophagocytosis in bone marrow and other reticuloendothelial systems. It has two forms: primary and secondary. The precise pathogenesis of HPS is unclear but a dysregulation of macrophage-lymphocyte interactions with subsequent increases in the levels of both T-cell-derived and macrophage-derived cytokines has been suggested. Cardinal symptoms of HPS are prolonged high fever, hepatosplenomegaly, cytopenias, lymphadenopathy and neurological symptoms. In this report, we present a case Systemic Lupus Erythematosus associated with HPS and acute pancreatitis.